ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA SEKOLAH MENENGAH KEJURUAN (SMK) SAHID MELANJUTKAN STUDI DI FAKULTAS EKONOMI DAN BISNIS ISLAM INSTITUT AGAMA ISLAM SAHID BOGOR - Hinka Lutfiah; Rully Trihantana; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
The decision to continue studying at a university can be interpreted as a process of searching and taking steps to get results in continuing or continuing higher education levels. This is motivated by the existence of different student factors in choosing a study program and choosing a college to continue the student's education. Universities must be able to know what factors can influence students to continue higher education. This study uses quantitative research methods, this research data uses secondary data and primary data, the sample taken is 30 students of SMK Sahid Bogor which is a saturated sample, the data collection techniques in this study are questionnaires, websites, and documentation. Based on the results of hypothesis testing, partially that interest and motivation factors have no effect on the decision of Sahid Vocational School students to continue their studies at the Faculty of Islamic Business Economics, Sahid Islamic Institute, while socioeconomic status factors influence the decision to continue their studies. Simultaneously the factors of interest, motivation, and socioeconomic status have a significant and significant effect on the decision to continue the study, the coefficient of determination is shown by the R Square value of 0.257 or 25.7%.